Enhanced control of unstable cascade systems using direct synthesis approach. (15th March 2021) - Atif Siddiqui, Mohammad; Anwar, M.N.; Laskar, S.H.
Highlights: A controller design method is presented for wide range of unstable cascade process. The method is based on the direct synthesis scheme for both the loops. Secondary controller is designed for the desired load disturbance rejection. Primary controller is designed for desired set-point response. The efficacy of the method has been validated through simulation examples. Abstract: This paper presents a controller design method for the open-loop unstable process in the primary loop and the open-loop unstable, integrating and stable processes in the secondary loop of the simple cascade control configuration. The controller of the secondary loop and the primary loop is designed through a direct synthesis (DS) approach in the frequency domain for load disturbance rejection and set-point tracking, respectively. Moreover, a set-point filter is used to reduce unnecessary overshoot in servo tracking. The proposed method is applicable to a wide range of processes having unstable, integrating and stable dynamics in a unified way. It avoids the complexity of order reduction and dead time approximation of the plant. The simulation study illustrates that the present approach provides enhanced closed-loop performance as compared to the approaches recently reported in the literature.